Joint Estimation of Mark-up and Bargaining Power Parameters for Belgian Manufacturing - Sabien Dobbelaere (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
This paper applies several extensions of Hall's (1988) methodology to analyse imperfections in both the product and the labour market for firms in the Belgian manufacturing industry over the period 1988-1995. We investigate (1) the heterogeneity in mark-up and bargaining power parameters among 17 sectors within the manufacturing industry, (2) whether higher bargaining power parameters are associated with higher mark-ups and (3) whether both parameters are influenced by cyclical and competition effects. Our GMM results indicate that ignoring imperfection in the labour market leads to an underestimation in the price-cost margin of Belgian manufacturing firms. These findings are confirmed in the sectoral analysis. As expected, higher bargaining power parameters are associated with higher price-cost margins at the sectoral level. We find that both the mark-up and the bargaining power parameter move procyclically. Finally, after controlling for cyclical effects, our results show that the introduction of a new competition policy in Belgium in 1993 has exerted a statistically significant negative effect on the price mark-ups, leaving the bargaining strength of the workers unchanged. Hence, the stringent competition law seems to have disciplined firms?pricing behaviour.
Keywords: C23; D21; J50; K21; L13; 330; Efficient Bargaining; Price Setting; Market Power; Competition Policy; Enterprise Behaviour; Verarbeitendes Gewerbe; Lohnverhandlungen; Gewerkschaftsmitgliedschaft; Betriebliche Preispolitik; Marktmacht; Belgien